Bioresorbable Scaffolds: Current Evidences in the Treatment of Coronary Artery Disease - BHARGAV DAVE (Journal of Clinical and Diagnostic Research, 2016)
Percutaneous coronary revascularization strategies have gradually progressed over a period of last few decades. The advent of newer generation drug-eluting stents has significantly improved the outcomes of Percutaneous Coronary Intervention (PCI) by substantially reducing in-stent restenosis and stent thrombosis. However, vascular inflammation, restenosis, thrombosis, and neoatherosclerosis due to the permanent presence of a metallic foreign body within the artery limit their usage in complex Coronary Artery Disease (CAD). Bioresorbable Scaffolds (BRS) represent a novel approach in coronary stent technology. Complete resorption of the scaffold liberates the treated vessel from its cage and restores pulsatility, cyclical strain, physiological shear stress, and mechanotransduction. In this review article, we describe the advances in this rapidly evolving technology, present the evidence from the pre-clinical and clinical evaluation of these devices, and provide an overview of the ongoing clinical trials that were designed to examine the effectiveness of BRS in the clinical setting.